Asymmetric frontiers, environmental insecurity and migrations (2017)
In our planet exist two dissimilar but connected worlds, namely: Developed nations being mostly selectively protected with strong frontiers mainly against negative fluxes, including poor migrants and epidemics, and underdeveloped nations which have weak barriers against dangerous unilateral fluxes. A main effect of the existence of asymmetric intrastate and interstate frontiers is that countryside and peripheral countries are destined to be stores and suppliers of natural renewable and non-renewable resources, and deposits of dangerous wastes and contaminants. Therefore, most of its poor population is confined in settings of growing ecological insecurity. This kind of globalization implies transference of environmental insecurity from opulent regions to peripheral zones, and this situation exacerbates the natural entropic process of the entire planet, due the growing levels of depletion and contamination of natural resources in a finite and vulnerable earth.